TO INCREASE THE INTEREST OF YOUNGER STUDENTS IN SPORTS CIRCLES THROUGH THE FORMATION OF SPIRITUAL MORAL VALUES - Halmatova Nasiba Bozorboevna (American Journals, 2024)
This article covers information on the growth and development of the body of Primary School students, physical rehabilitation of children, rehabilitation-oriented autoreflex special physical exercises,the formation of spiritual moral values, increased physical activity, yoga poses and control exercises, the formation of the correct figure.
Keywords: Wellness, spiritual, moral values, exercise, active movement, growth, bodily qualities, physical activity, correct posture, optimization, mental ability.